COMPLIANCE RATES OF RECOMMENDED VACCINES AMONG MIDDLE SCHOOL STUDENTS - Campbell, Stefanie (My University, 2019)
This study evaluated the vaccination rates of recommended vaccines in middle school aged adolescence. The study looked at one middle school consisting of students in 6th, 7th, and 8th grades. The recommended vaccines include the human papillomavirus vaccine (HPV) and Meningococcal vaccine (MCV). Vaccination rates of required vaccines were not included in this study. Required vaccines for adolescences in grades 7-12 in the state of Kansas include; Tdap (Tetanus, diphtheria, pertussis), IPV (Polio), MMR (Measles, Mumps, Rubella), Varicella (Chickenpox), and Hepatitis B. This study also does not evaluate the rates of influenza vaccinations which is a recommended annual vaccine. A sample of 888 students was assessed to compare the compliance rates of one single Kansas school district with data from regional and national reports. This data was collected from USD 475 Junction City Middle School. Gender of the students was not revealed in the collected data, so sex determination between regional and national data was also omitted. The vaccination rates of HPV and MCV are important for public health. Even though these vaccines are not required, they can prevent very serious diseases among middle school aged children and even into adulthood. Results from this study indicate that vaccine coverage with HPV and MCV are decreased in USD 475 and Kansas when compared to the national data. Future efforts of intervention should be considered to increase the overall compliance of obtaining both vaccines to prevent further disease transmission.
Keywords: vaccination rates; HPV